The formal act of defection from the Catholic Church - Jabłońska, Paulina (Prawo Kanoniczne, 2020)
The article presents problem of a formal act of defection from the Catholic Church. Article describe regulations based on the Catholic Church documents such as: Code of Canon Law (1983), Pontifical Council for Legislative Texts (2006), motu proprio of Benedict XVI Omnium in mentem (2009) and the documents of Polish Bishops Conference. At the end of the article it describes the effects of the formal act of defection from the Catholic Church.